Phraseologization as a process of semantic change - Elena Sánchez López (Universitat Autònoma de Barcelona, 2015)
On the one hand, phraseology has sorted out how to describe Phraseological meaning from a synchronic perspective. On the other, cognitive diachronic linguistics has thoroughly described the process of semantic change and the mechanisms leading to it, but mostly focusing on grammaticalization. The aim of the present paper is to bring together these two perspectives in order to account for the existence of Phraseological Units, i.e. the emergence of Phraseological Meaning. This integration of perspectives will require a well defined theoretical framework. First of all, we will establish the definition of PhU and the scope of Phraseological meaning. Then, we will compare grammaticalization to phraseologization process. In this comparison, we will pay special attention to the new role assigned to inference as a mechanism leading to semantic change. Finally, we will apply the developed theoretical framework to an actual PhU: al peu de la lletra.